STUDI KOMPARATIF RISIKO SISTEMIK ANTARA BANK SYARIAH DAN BANK KONVENSIONAL DI INDONESIA: PENDEKATAN TAFSIR TEMATIK TERHADAP SURAH AL-BAQARAH - Oktavera Rizki; Azhari Akmal Tarigan; Mustapa Khamal Rokan; Andri Soemitra; Yusrizal (At-Tanmiyah Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to compare systemic risk between Islamic banks and conventional banks in Indonesia by employing a thematic exegesis approach (tafsīr al-mawḍū‘ī) to selected Qur’anic verses in Surah Al-Baqarah, specifically verses 30, 219, 220, 245, 275, 276, and 282. These verses address fundamental themes related to finance, justice, debt relationships, usury (ribā), charitable giving (ṣadaqah), and equitable wealth distribution within the framework of Islamic economic principles. By integrating qualitative analysis drawn from classical and contemporary Qur’anic exegesis—including Tafsīr al-Ṭabarī, Ibn Kathīr, and Tafsīr al-Māwardī—with insights from modern economic literature, this study highlights the fundamental distinctions between Sharī‘ah-based financial principles and conventional banking practices in relation to financial system stability. The findings indicate that the Islamic financial system embodies inherent mechanisms capable of mitigating systemic risk, notably through the prohibition of ribā, the implementation of profit-and-loss sharing arrangements, and the moral obligation to uphold charitable redistribution and social justice. In contrast, interest-based conventional financial systems tend to exacerbate economic inequality and amplify vulnerability to financial crises. These findings reinforce the contemporary relevance of Qur’anic values in informing financial stability policies within modern economic systems.